The eukaryotic linear motif resource ELM: 10 years and counting - Dinkel, Holger; Van Roey, Kim; Michael, Sushama; Davey, Norman E.; Weatheritt, Robert J.; Born, Diana; Speck, Tobias; Krüger, Daniel; Grebnev, Gleb; Kubań, Marta; Strumillo, Marta; Uyar, Bora; et al. (Nucleic acids research, 2014)
Abstract. The eukaryotic linear motif (ELM http://elm.eu.org) resource is a hub for collecting, classifying and curating information about short linear motifs